2021
DOI: 10.21303/2461-4262.2021.001824
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tool wear and surface roughness in high-speed milling process of aluminum alloy Al6061

Abstract: In this study, the influence of cutting parameters and machining time on the tool wear and surface roughness was investigated in high-speed milling process of Al6061 using face carbide inserts. Taguchi experimental matrix (L9) was chosen to design and conduct the experimental research with three input parameters (feed rate, cutting speed, and axial depth of cut). Tool wear (VB) and surface roughness (Ra) after different machining strokes (after 10, 30, and 50 machining strokes) were selected as the output para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(34 reference statements)
0
3
1
Order By: Relevance
“…In another series of experiments examining the effect of machining time as well as cutting parameters on tool wear and surface roughness during high-speed milling of Al6061 with face carbide inserts, it was found that the most significant factors in connection with surface roughness were the axial depth of cut and feed rate [25]. In the present study, no such dependency was found.…”
Section: The Effect Of Axial Depth Of Cut On Surface Roughnesscontrasting
confidence: 56%
See 1 more Smart Citation
“…In another series of experiments examining the effect of machining time as well as cutting parameters on tool wear and surface roughness during high-speed milling of Al6061 with face carbide inserts, it was found that the most significant factors in connection with surface roughness were the axial depth of cut and feed rate [25]. In the present study, no such dependency was found.…”
Section: The Effect Of Axial Depth Of Cut On Surface Roughnesscontrasting
confidence: 56%
“…Another example of research in this field involved investigating how the relative position of the face mill and the machined piece, as well as the milling kinematics (conventional vs climb), impact the various components of cutting force and the surface roughness when performing face milling with a milling width greater than the diameter of the cutter, as opposed to them being equal [24]. Another study investigated how changing the cutting parameters and machining time affects tool wear and surface roughness during milling [25]. In the case of another study, a high-feed milling cutter allowed for a two-fold increase in the volume of cut and higher machining efficiency but resulted in greater surface roughness and vibration amplitudes [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, traditional machining is considered to have low e ciency, especially from the perspectives of machining cost and surface quality. As an alternative, high-speed milling can provide surface quality and gloss comparable to those obtained with a grinding method [2]. Moreover, high-speed milling allows us to obtain a better surface-roughness finish and better geometric accuracy than traditional machining methods.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on high-speed milling have commonly been based on mathematical models and single-objective optimization [2,27,28]. However, to our knowledge, research on multiobjective optimization in high-speed milling 6061 aluminum alloy is rare, especially with a combination of machine learning and multiobjective optimization algorithms.…”
Section: Introductionmentioning
confidence: 99%